Influence of f-MLP, ACTH(1-24) and CRH on in vitro chemotaxis of monocytes from centenarians - Genedani, Susanna; Filaferro, Monica; Carone, Chiara; Ostan, Rita; Bucci, Laura; Cevenini, Elisa; Franceschi, Claudio; Monti, Daniela (Neuroimmunomodulation, 2008)
The lifelong exposure to a variety of stressors activates a plethora of defense mechanisms, including the hypothalamic-pituitary-adrenal axis which releases neuropeptides affecting the immune responses. Here, we report data on the capability of monocytes from young subjects and centenarians to migrate towards chemotactic stimuli (formyl-methionyl-leucyl-phenylalanine, f-MLP; adrenocorticotropic hormone, ACTH, and corticotrophin-releasing hormone, CRH). Plasma levels of ACTH, CRH and cortisol were measured as an index of ongoing stress response. Monocyte chemotaxis towards f-MLP (10(-8)M), ACTH(1-24) (10(-14) and 10(-8)M) and CRH (10(-14) and 10(-8)M) was evaluated in vitro in young subjects (n = 8, age range 25-35 years) and centenarians (n = 9, age >100 years) and expressed as chemotactic index. In 9 young subjects and 6 centenarians, plasma levels of cortisol, ACTH and CRH were measured. Monocyte chemotaxis towards f-MLP, ACTH(1-24) and CRH (10(-8)M) was well preserved in centenarians, except when the lowest concentration of CRH was used. CRH, ACTH and cortisol plasma levels were significantly higher in centenarians than in young subjects. The capability of monocytes from centenarians to respond to chemotactic neuropeptides is well preserved. The decreased responsiveness to the lowest concentration of CRH might be due to downregulation of CRH receptors or to defects in the intracellular signal transduction pathway. The high plasma levels of cortisol, CRH and ACTH in centenarians indicate an activation of the entire stress axis, likely counteracting the systemic inflammatory process occurring with age. This activation fits with the hypothesis that lifelong low-intensity stressors activate ancient, hormetic defense mechanisms, favoring healthy aging and longevity.